The Emerging Role of Neutrophil Extracellular Traps (NETs) in Tumor Progression and Metastasis - Masucci, Maria Teresa; Minopoli, Michele; Del Vecchio, Silvana; Carriero, Maria Vincenza (Frontiers in Immunology, 2020)
Neutrophil Extracellular Traps (NETs) are net-like structures composed of DNA-histone complexes and proteins released by activated neutrophils. In addition to their key role in the neutrophil innate immune response, NETs are also involved in autoimmune diseases, like systemic lupus erythematosus, rheumatoid arthritis, psoriasis, and in other noninfectious pathological processes, as coagulation disorders, thrombosis, diabetes, atherosclerosis, vasculitis and cancer. Recently, a large body of evidence indicates that NETs are involved in cancer progression and metastatic dissemination, both in animal models and cancer patients. Interestingly, a close correlation between cancer cell recruitment of neutrophils in the tumor microenvironment (Tumor Associated Neutrophils. TANs) and NET formation has been also observed either in primary tumors and metastatic sites. Moreover, NETs are able to catch circulating cancer cells and promote metastasis, as well. Furthermore, NETs have been reported to awake dormant cancer cells, thus causing tumor relapse and metastasis. This review will primarily focus on the pro-tumorigenic activity of NETs in tumors highlighting their ability to serve as potential target for cancer therapy.